Pitt’s theorem for operators between general Lorentz sequence spaces - López Molina, J. A. (MATHEMATICA SCANDINAVICA, 2002)
We characterize the pairs of general Lorentz sequence spaces ^u,v( u), ^p,q(μ), 0 < u, v, p, q < ∞ such that all continuous linear maps from the first space into the second one are compact.